2018
DOI: 10.4103/jrms.jrms_463_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of pegylated granulocyte-colony stimulating factor and granulocyte-colony stimulating factor on cytopenia induced by dose-dense chemotherapy in breast cancer patients

Abstract: Background:Myelosuppression is one of the frequent side effects of chemotherapy in breast cancer patients. Granulocyte-colony stimulating factor (G-CSF) and pegylated G-CSF are used for the prevention of neutropenia after chemotherapy. Pegylated G-CSF has longer half-life of action and can be used as a single dose in comparison to G-CSF. The aim of this study is to compare the grade of cytopenia and side effects between G-CSF and biosimilar pegylated G-CSF in breast cancer patients treated with dose-dense chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…6,14,17,18 Daily injections are used as G-CSF has a half-life of a 3-4 h, which can be extended by conjugating G-CSF with polyethylene glycol (PEGylation). 19,20 However, immune responses against PEG have been demonstrated to enhance clearance of PEG-G-CSF in an antibody-dependent manner. 21 As multiple cycles of PEG-G-CSF treatment are common, long-term treatment could be rendered ineffective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,17,18 Daily injections are used as G-CSF has a half-life of a 3-4 h, which can be extended by conjugating G-CSF with polyethylene glycol (PEGylation). 19,20 However, immune responses against PEG have been demonstrated to enhance clearance of PEG-G-CSF in an antibody-dependent manner. 21 As multiple cycles of PEG-G-CSF treatment are common, long-term treatment could be rendered ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia is typically treated as an emergency and, in a subset of patients, the risk of neutropenia may be prophylactically addressed with post‐HSCT subcutaneous injection of recombinant human G‐CSF (filgrastim) to facilitate recovery 6,14,17,18 . Daily injections are used as G‐CSF has a half‐life of a 3–4 h, which can be extended by conjugating G‐CSF with polyethylene glycol (PEGylation) 19,20 . However, immune responses against PEG have been demonstrated to enhance clearance of PEG‐G‐CSF in an antibody‐dependent manner 21 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, serum concentrations are sustained throughout the duration of neutropenia. Peg GCSF can be used as single dose in comparison to GCSF, and guidelines re ning the use of peg GCSF for prevention of chemotherapy induced febrile neutropenia has been published [11,12]. In a previous study to compare peg GCSG and GCSF in order to prevent neutropenic fever during consolidation with HIDAC, it was concluded that GCSF compared to peg GCSF was found to be statistically signi cantly associated with increased risk of hospitalization [13].…”
Section: Introductionmentioning
confidence: 99%